Probing the electrochemical properties of exclusion zone water - Yee, Chut-Ngeow; Raymond Ooi, C.H.; Tan, Luck-Pheng; Tang, Nyiak-Tao (Penerbit Universiti Kebangsaan Malaysia, 2025)
The presence of solute-free zones, called the exclusion zones (EZ) near water interfaces, is a phenomenon that has been extensively studied. While the EZ is shown to be negatively charged, it is balanced by an adjacent region that is rich in positive ions. This paper investigates this twin characteristic of EZ on electrical conductivity. We show that EZ has a strong inhibitory effect on electrical flow, especially the negative current, providing additional evidence to its structural integrity and rigidity. More interesting is the positive ion-rich region adjoining the EZ, we show this region is a highly conductive surface that facilitates the flow of negative current.